Effects of Kuroshio Intrusions on the atmosphere northeast of Taiwan Island. Issue 5 (6th March 2015) - Chow, Chun Hoe; Liu, Qinyu; Xie, Shang‐Ping
Abstract: The Kuroshio loses bathymetric support off northeast Taiwan Island, causing large variability in its path. The resultant covariability of sea surface temperature (SST) and the lower atmosphere is investigated using satellite observations. In winter and spring off northeast Taiwan Island, the intrusions of warm Kuroshio water onto the continental shelf cause a large increase in local SST, intensify the northeasterly monsoonal winds, and lead to the increases in water vapor and rainfall. Key to this air‐sea interaction is the existence of anomalous heat advection by the Kuroshio intrusions. The Kuroshio intrusions are partly due to westward propagating ocean eddies east of Taiwan Island with a lead time of 3 weeks, hinting at the possibility of improved weather prediction near northeast Taiwan Island by considering ocean variability east of Taiwan Island. Key Points: Kuroshio intrusions affect local climate Kuroshio intrusions are related to ocean wave propagation Results can be used to improve weather prediction in northeast Taiwan Island